Hybrid Energy (Thermoelectric Generator-Archimedes Screw Turbine) Study and Experiment as a Green Energy Generator Based on the Internet of Things (IoT) - Roy Lamrun Sianturi; Wilson Sabastian Nababan; Siwan E Parangin angin (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2024)
The heat energy from the hot water source of Mount Sinabung can be used as a source of electrical energy before being channeled as a source of hot water baths. The hot water flow has a fairly high temperature and a flow rate that can be converted into a source of electricity generation using a Micro Hydro Power Plant (PLTMH) and Thermoelectric Generator (TEG). This data collection was simulated using a heat source designed in a reservoir and a cold water flow that is channeled into the PLTMH-TEG system space as a source of temperature delta. This paper aims to study the TEG series TEG1-199-1.4-0.5 and the Archimedes screw Turbine (PLTMH) as a Hybrid Generator (Green Energy). Data analysis was carried out to calculate the system power output, battery charging time, and efficiency of the TEG and PLTMH. Data analysis in this study applies the Internet of Things (IoT). Test data shows that the maximum output parameter of the PLTMH during testing, obtained a maximum voltage of 20.42 Vdc. The maximum current is 759.75 mA and the maximum water discharge is 2.31 m3/s. In the TEG system, the power generated by the TEG is 20.64 watts at a temperature difference of 70.5˚C. It is concluded that the higher the amount of discharge flowing into the Archimedes turbine system and the temperature difference absorbed by the TEG, the greater the power that will be generated and vice versa.